Enhancing analgesic techniques for the management of perioperative analgesia in dogs and cats : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Manawatu, Palmerston North, New Zealand - Sawicki, Robert (Massey University, 2025)
Effective pain management is a cornerstone of veterinary care. However, challenges persist in optimising perioperative analgesia across diverse clinical situations and in different species. In a series of studies that form the backbone of this thesis, the electroencephalogram (EEG) and postoperative pain scores were used to evaluate a variety of drugs administered in the perioperative period and their analgesic efficacy in both feline and canine patients undergoing a range of surgical procedures resulting in nociception and postoperative pain. Premedication involves the administration of an appropriate analgesic or combination of drugs to blunt nociceptive inputs during the intraoperative period, ideally before nociception begins. One study used the EEG to assess the efficacy of three commonly used opioids—morphine, buprenorphine, and methadone–as premedication in healthy cats undergoing castration. The results demonstrated that while all three opioids were effective in mitigating nociceptive input, methadone was significantly more effective than either morphine or buprenorphine. Beyond the efficacy of individual premedication agents, the interactions between multiple drugs administered in combination are also critical in shaping intraoperative and postoperative analgesia. One study investigated EEG indices of nociception in cats undergoing castration, examining how vatinoxan, an α₂-adrenoceptor antagonist, influenced the analgesic efficacy of dexmedetomidine, an α₂-adrenoceptor agonist, when given alone or in combination, with or without morphine. The findings indicated no significant attenuation of dexmedetomidine’s antinociceptive effects when vatinoxan or morphine were added. Interestingly, high-dose morphine alone provided superior antinociception compared to dexmedetomidine, either alone or in combination with morphine and/or vatinoxan. In dogs, intraoperative nociception and postoperative pain are often managed using multimodal analgesia-combinations of drugs designed to enhance analgesic efficacy and reduce side effects. One study evaluated intraoperative nociceptive indices and postoperative pain scores in dogs undergoing castration, comparing the effects of systemically administered morphine, locally administered bupivacaine via incisional block, and their combination to effectively control nociception and postoperative pain. While both morphine and bupivacaine alone effectively reduced intraoperative nociception, bupivacaine was superior in managing postoperative pain. However, the combination of both systemically administered morphine and locally administered bupivacaine proved most effective, completely suppressing intraoperative nociception. Postoperative analgesic efficacy is influenced not only by the choice and combination, of drugs but also by the route of administration. This is particularly relevant when methods are adopted from human applications. A study assessing transdermally administered buprenorphine in dogs undergoing tibial tuberosity advancement orthopaedic surgery for the correction of cranial cruciate ligament rupture showed that dogs receiving buprenorphine patches had significantly lower postoperative pain scores than those in the control group. These results support transdermal buprenorphine as a useful and effective alternative for postoperative pain management in dogs undergoing orthopaedic procedures. These studies demonstrate that perioperative analgesic efficacy can be significantly enhanced by carefully considering key parameters, including drug selection, appropriate dosing, multimodal combinations, and the most suitable route of administration for the specific procedure.
Keywords: veterinary surgery, pain, nociception, feline, canine, veterinary medicine, opioid, analgesia; 300901 Veterinary anaesthesiology and intensive care